The Role of Urinary Potassium Examination on the Progressivity of Chronic Kidney Disease: A Narrative Literature Review - Rezki Sadeli; Harnavi Harun; Drajad Priyono; Deka Viotra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Kidneys play an important role in potassium homeostasis. The important role of the kidneys in maintaining potassium balance is reflected in the high level of potassium disturbances in patients with decreased kidney function, especially patients with severely decreased renal function and patients who have comorbidities, such as diabetes, hypertension, or heart failure. Chronic kidney disease is characterized by abnormalities of kidney structure or function that persist for more than 3 months, have many complex causes, and have a major impact on global health status. There are several methods to measure the amount of potassium intake consumed, including a food frequency questionnaire, dietary recall, temporary urine potassium examination, and 24-hour urine potassium examination. The standard gold measurement for evaluating urinary potassium excretion is through 24-hour urine collection. This literature review aims to describe the role of urinary potassium excretion in assessing the progression of chronic kidney disease.